LEVEL OF STRESS, SELF-ADJUSTMENT, AND QUALITY OF LIFE FOR SINGLE FATHER - Moh. Fahmi Saputra; Diah Krisnatuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Single parents are associated with unique adjustment needs because of the multiple roles they accept, so heavy burdens, especially for single fathers, can trigger stress and affect their quality of life. This study aims to analyze the effect of stress levels and adjustment on the quality of life of single fathers. This study involved 60 single fathers living in villages and cities distributed throughout Indonesia using a purposive sampling technique with data collected through an online questionnaire google form. Processing data using Microsoft Excel and SPSS version 25 with descriptive analysis, different independent sample t-tests, Kendalls tau-b and Pearson correlation test, and multiple linear regression test. The results showed that the variables of stress level and quality of life were in the medium category, while the adjustment variable was in the low category. The relationship test results showed a significant relationship between stress levels (negative), adjustment (positive), and quality of life. The regression test results showed a significant negative effect of stress levels and a significant positive self-adjustment on the quality of life of single fathers, meaning that the lower the stress level and the better the adjustment, the higher the quality of life of single fathers. The single father feels that with his current conditions, his quality of life can still be controlled, although sometimes he has some obstacles. In the future, it is hoped that this can be done regarding other variables that affect the quality of life, as well as exploring the comparison of single fathers and single mothers.